Psychological and Psychosomatic Symptoms of Second Victims of Adverse Events: a Systematic Review and Meta-Analysis. Issue 2 (June 2020) - Busch, Isolde M.; Moretti, Francesca; Purgato, Marianna; Barbui, Corrado; Wu, Albert W.; Rimondini, Michela
Abstract : Objectives: Despite growing interest in the second-victim phenomenon and greater awareness of its consequences, there has not been a meta-analysis quantifying the negative impact of adverse events on providers involved in adverse events. This study systematically reviewed the types and prevalence of psychological and psychosomatic symptoms among second victims. Methods: We conducted a systematic review of nine electronic databases up to February 2017, without restrictions to publication date or language, examining also additional sources (e.g., gray literature, volumes of journals). Two reviewers performed the search, selection process, quality assessment, data extraction, and synthesis. We resolved disagreements by consensus and/or involving a third reviewer. Quantitative studies on the prevalence of psychological and psychosomatic symptoms of second victims were eligible for inclusion. We used random effects modeling to calculate the overall prevalence rates and the I 2 statistic. Results: Of 7210 records retrieved, 98 potentially relevant studies were identified. Full-text evaluation led to a final selection of 18 studies, based on the reports of 11, 649 healthcare providers involved in adverse events. The most prevalent symptoms were troubling memories (81%, 95% confidence interval [CI] = 46–95), anxiety/concern (76%, 95% CI = 33–95), anger toward themselves (75%, 95% CI = 59–86), regret/remorse (72%, 95% CI = 62–81), distress (70%, 95% CI = 60–79), fear of future errors (56%, 95% CI = 34–75), embarrassment (52%, 95% CI = 31–72), guilt (51%, 95% CI = 41–62), and sleeping difficulties (35%, 95% CI = 22–51). Conclusions: Second victims report a high prevalence and wide range of psychological symptoms. More than two-thirds of providers reported troubling memories, anxiety, anger, remorse, and distress. Preventive and therapeutic programs should aim to decrease second victims' emotional distress. Abstract : Supplemental digital content is available in the text.